Genetic Characterization of Staphylococcus aureus Isolated from Retail Meat in Riyadh, Saudi Arabia - Raji, Muhabat A.; Garaween, Ghada; Ehricht, Ralf; Monecke, Stefan; Shibl, Atef M.; Senok, Abiola (Frontiers in Microbiology, 2016)
Limited data exists from the Gulf Cooperation Council states on the prevalence and population dynamics of Staphylococcus aureus colonizing livestock or contaminating retail meat. This study was designed to determine the presence and genetic characteristics of Staphylococcus aureus isolated from raw retail meat sold in Riyadh, Saudi Arabia. Over a period of 9 months, different raw retail meat types were aseptically processed using the double broth enrichment technique, characteristic colonies from chromogenic and mannitol salt agar were further identified using conventional methods. Susceptibility to 9 antibiotics was determined using the disc diffusion technique. Interpretation of inhibition zone was done according to Clinical and Laboratory Standards Institute guidelines. Molecular characterization was carried out using the StaphyType DNA microarray technology. Twenty-five meat samples yielded Staphylococcus aureus isolates. Camel meat had the highest contamination rate with Methicillin resistant Staphylococcus aureus (MRSA) (20.8%) and Methicillin susceptible Staphylococcus aureus (29.2%), while poultry meat had the least contamination rate with MRSA (3.4%). The MRSA isolates were grouped into 4 clonal complexes (CCs) namely CC1-MRSA-IV/SCCfus (n=2), CC15-MRSA-V/SCCfus (n=4), CC80-MRSA-IV/PVL+ (n=5) and CC88-MRSA-IV/PVL+ (n=2). All CC15-MRSA-V/SCCfus isolates were obtained from camel meat. This is the first study to demonstrate the novel CC15-MRSA-V/SCCfus in retail camel meat. We recommend that surveillance studies should be incorporated in public health and food hygiene programs.